Identification of MIMO Magnetic Bearing System Using Continuous Subspace Method with Frequency Sampling Filters Approach - PPKEE, Pusat Pengajian Kejuruteraan Elektrik & Elektronik (2011)
As mentioned in NASA spinoff, “magnetic bearings support moving machinery without physical contact. They can levitate a rotating shaft and permit relative motion without friction or wear. Long considered a promising advancement, they are now moving beyond promise into actual service in such industrial applications as electric power generation, petroleum refining, machine tool operation and natural gas pipelines”